Exploring Pull Factors of Travel Motivation: An Exploratory Study in Sylhet Region - Hani, Fathema Farjana (Asian Business Review, 2016)
Bangladesh has a massive potential to flourish its tourism sector. As it have spectacular resources to present. This study analyzes the importance level of motivational pull factors that affect tourists’ decision when they chose a destination for tourism. 100 questionnaires were completed using face-to-face and telephone interview to collect pre and post-visit information. Data have gathered from the tourists who visited from outside of Sylhet and also from greater Sylhet Division by structured questionnaires. The study demonstrates that highest importance level gained by the availability of public toilet in the tourist spot (mean value 4.64). Gradual importance is attained from the elements- easily reached and cleanliness of the destination, pleasant and safe accommodation, personal security, prices of different products, availability of hygiene food and beverages, availability of recreation facilities, reasonable rent of accommodation, and shopping facility After examining the post visit opinion found some elements are treated the negative e.g. price of various products (food, drink, handicrafts, etc.), availability of public toilet, availability of different recreation facility (Water Park, sports facility, night life, etc.), and shopping facility. This study has an extensive implication for further research in tourism.
Keywords: Tourism; Pull factors; Importance level; Negative elements; Sylhet Division